Description Of Community Knowledge And Behavior Level On Healthy Latrine Ownership In Kubu Village - Syafaria Meilianti; Yulia; Susilawati (Jurnal teknologi Kesehatan Borneo, 2021)
One of the important efforts to improve health status was the procurement of a healthy environment for the community, one of which was having a healthy latrine. Owning a latrine was included in the basic sanitation needed to create a clean and healthy environment. With the availability of latrines that met health requirements it could avoid environmental-based diseases, such as typhoid, paratyphoid, dysentery and diarrhea. This study aimed to describe the level of knowledge and behavior of the community towards the ownership of healthy latrines in Kubu Village, Kubu District, Kubu Raya Regency. This type of research used descriptive research. The research population was 1583 families and the sample taken was 94 families using the Slovin formula. The results of this study indicated the level of knowledge was not good (70.2%), good knowledge (29.8%), good behavior (63.8%), bad behavior (36.2%). Ownership of healthy latrines (82.7%), ownership of healthy latrines (17.3%). The conclusion from the results of this study was ownership of healthy latrines has a relationship with respondents' knowledge and affects community behavior in accessing basic sanitation